ASSESSMENT OF SPECIATION AND ANTIFUNGAL SUSCEPTIBILITY TESTING IN THE INTENSIVE CARE UNIT: AN OBSERVATIONAL CROSS-SECTIONAL STUDY DESIGN. - Shome, Bhuvan; Sharma, Ashok Kumar; Seema, Kumari; Kumar, Abhay; Kumar, Manoj; Boipai, Manju (Student's Journal of Health Research Africa, 2023)
Objectives: This study aims to investigate the epidemiology of Candidemia in patients admitted to Intensive Care Units (ICUs), focusing on the distribution of species, antifungal susceptibility patterns, and demographic factors. Methods: The study was carried out for 1 year at the Department of Microbiology, Rajendra Institute of Medical Sciences in Jharkhand, India, and collected 817 blood samples from ICU-admitted patients with signs of sepsis. Using various tests, including germ tube tests and MALDI-TOF mass spectrometry, the study identified Candida species and conducted antifungal susceptibility tests with the VITEK-2 system. The results, categorized as vulnerable, intermediate, or resistant, provided insights into the incidence rates and sensitivity of Candidemia in the studied population. Results: The study revealed a Candidemia incidence of 9.57 % among 292 positive blood cultures from ICU-admitted patients. Non-candida albicans predominated at 71.42 %, with Candida tropicalis species encompassing over 28.57 % of the cases. Antifungal susceptibility testing showed all species were vulnerable to the antifungals employed in this study, with C. krusei displaying innate resistance to fluconazole. Conclusion: This study highlights the changing epidemiology of Candidemia, with a notable rise in non-candida albicans species, especially in pediatric patients, particularly infants. Despite these shifts, the identified Candida isolates demonstrated overall susceptibility to tested antifungals, emphasizing the significance of precise species-level confirmation and antifungal vulnerability testing for tailored therapeutic approaches in the ICU setting. Recommendation: This study recommends continuous monitoring of local Candida species distribution, presumptive identification, and confirmation for early empirical therapy. Moreover, coupled with regular antifungal susceptibility testing to enhance treatment outcomes in vulnerable patient populations.